High-dose Interleukin-2 for the Treatment of Metastatic Renal Cell Carcinoma: A Retrospective Analysis of Response and Survival in Patients Treated in the Surgery Branch at the National Cancer Institute Between 1986 and 2006 - Klapper, Jacob A. (2008)
BACKGROUND: The treatment of metastatic renal cell carcinoma (RCC) with high-dose interleukin-2 (HD IL-2) has resulted in durable tumor regression in a minority of patients. The current study presents the authors’ 20-year experience administering this immunotherapeutic agent. METHODS: Patients with metastatic RCC (n = 259) were treated with HD IL-2 alone from January 13, 1986 through December 31, 2006 at the Surgery Branch of the National Cancer Institute. Potential predictive factors for response and survival, both pretreatment and treatment-related, were first subjected to univariate analysis and then to multivariate logistic regression or a Cox proportional hazards model. Finally, the authors investigated Memorial Sloan-Kettering Cancer Center (MSKCC) prognostic factors for survival to assess their predictive value in the patient population in the current study. RESULTS: A total of 23 patients experienced a complete response and 30 patients achieved a partial response, for an overall objective response rate of 20%. All partial responders had developed disease recurrence at the time of last follow-up, but only 4 complete responders had experienced disease recurrence by that time. Despite toxicities, only 2 patients developed treatment-related mortalities over this same time period. A higher baseline weight (P =.05) and MSKCC prognostic factors (P = .02) were found to be the variables most associated with response. For survival >4 years and overall survival, several pretreatment and treatment-related factors maintained significance, but none more so than response (P <.0001). CONCLUSIONS: HD IL-2 can induce complete tumor regression in a small number of patients, and many patients have experienced extended disease-free intervals. Given its relative safety, HD IL-2 should still be considered a first-line therapy in patients with metastatic RCC who have an overall good performance status.